People's Republic of China Financial Sector Assessment Program : CPSS Core Principles for Systemically Important Payment Systems - International Monetary Fund (World Bank, Washington, DC, 2017)
People's Bank of China (PBC) has carried out a major and comprehensive reform of the China National Payments System (CNPS). The PBC implemented the China National Advanced Payment System (CNAPS), which consists of the High-Value Payment System (HVPS) and the Bulk Electronic Payment System (BEPS). The HVPS system currently operates in a tiered way with a national processing center (NPC) and 32 local processing centers (LCPs). The HVPS system is interconnected to many trading, payments, and securities settlement systems (SSS) to allow for central bank money settlement. In addition, there is numerous cheque clearing houses around the country administered by the PBC local offices or delegated to banks. China Union Pay (CUP) handles the clearance of cards transactions whose balances are settled in the HVPS. Also automated clearinghouses (ACHs) and other systems handle clearance and settlement for a variety of payment instruments. The HVPS is a systemically important payment system, as it is the backbone of the national payments system in China. The HVPS handled transactions for a value of CY 804 trillion in 2009, approximately 24 times the Gross Domestic Product (GDP) value. Thus, the HVPS is being assessed against the ten Core Principles for Systemically Important Payment Systems (CPSIPS) of the Committee for Payment and Settlement Systems (CPSS) and the four responsibilities of the central banks in applying the CPSIPS. The BEPS is not currently a systemically important payment system. However, its importance for an efficient settlement of the interbank payment system is growing. The present document is the assessment of the systemically important payment systems in the People's Republic of China (PRC) based on the CPSS CPSIPS. The document also contains an analysis of some developmental issues related to the reform of the payments system as a whole. The assessment was conducted in the context of the first field mission of the Financial Sector Assessment Program (FSAP) to the PRC (June 2010).